Safety Grill with Fire Alarm System for Building Emergency Evacuation - Baharudin, Amirul Nurhakim; Danial Md Nor (Evolution in Electrical and Electronic Engineering, 2023)
Fire razes are a type of disaster that endangers the society’s property and personal safety. Nowadays, door and window grill systems on the market appear to be unsuitable because they are difficult to open, either for trapped people to rescue themselves or for firemen to assist them from outside. If a fire does occur, the system should be designed and equipped with appropriate levels of safety, such as prevention, early detection, and control means. Furthermore, the window grill should be simple to operate for adults, the elderly, children, and people with disabilities. As a result, the "safety grill with fire alarm system for building emergency action" project is proposed. Automatic window grill with fire alarm system is a prototype that uses the Durian UNO The DS18b20 Water Proof Temperature Sensor and an application (Blynk) to detect temperature rise and automatically unlock the window grill, activate the buzzer as an alarm. During the appearance of heat, this system operated automatically. Finally, this system added remote monitoring capabilities to the fire alarm system, allowing for real-time alerts and notifications to designated personnel in the event of an emergency.